2016
DOI: 10.1038/srep31783
|View full text |Cite
|
Sign up to set email alerts
|

Spin-wave propagation steered by electric field modulated exchange interaction

Abstract: Combined ab initio and micromagnetic simulations are carried out to demonstrate the feasibility on the electrical manipulation of spin-wave propagation in ultrathin Fe films. It is discovered that the exchange interaction can be substantially weakened under the influence of electric field applied perpendicular to the magnetic film surface. Furthermore, we demonstrate that the electric field modified exchange constant could effectively control the propagation of spin waves. To be specific, an external applied e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The feasibility of the electrical manipulation of spin-wave propagation in ultrathin Fe films through modulation of the exchange interaction by the electric field applied perpendicular to the magnetic film has been shown just recently in Ref. [29]. Of particular interest is also the effect of the voltage-controlled magnetic anisotropy, which manifests itself as a variation of the perpendicular magnetic anisotropy at the interface between a ferromagnetic metal and an insulator under the application of an interface voltage (see, e.g., [30,31] and references therein).…”
Section: Conclusion and Summarymentioning
confidence: 99%
“…The feasibility of the electrical manipulation of spin-wave propagation in ultrathin Fe films through modulation of the exchange interaction by the electric field applied perpendicular to the magnetic film has been shown just recently in Ref. [29]. Of particular interest is also the effect of the voltage-controlled magnetic anisotropy, which manifests itself as a variation of the perpendicular magnetic anisotropy at the interface between a ferromagnetic metal and an insulator under the application of an interface voltage (see, e.g., [30,31] and references therein).…”
Section: Conclusion and Summarymentioning
confidence: 99%
“…However, establishing spin wave-based transport as a viable solution for the next generation of electronics poses several challenges that need to be resolved to enable logic operations 7 (e.g. effective spin wave signal generation, propagation, control and detection) 5,6,[8][9][10][11][12] . At a fundamental level, there are still many outstanding questions concerning how magnetic properties and excitations evolve and emerge in low dimensional systems, such as thin films [13][14][15] .…”
mentioning
confidence: 99%
“…Up to now, it has been shown that the graded magnonic refractive index can be created by modification of the material properties, such as non-uniform saturation magnetization or exchange constant [ 44 , 45 , 46 , 47 ], the magnetic anisotropy [ 19 , 20 ] or the internal magnetic field [ 37 , 48 ]. This index can be also achieved by utilizing a non-uniform external magnetic field [ 39 , 49 , 50 , 51 ], electric field (voltage) [ 52 , 53 ] or temperature [ 54 , 55 ]. Therefore, graded-index magnonics are expected to overcome the current limitation of magnonics and pave feasible routes for the implementation of spin-wave devices.…”
Section: Introductionmentioning
confidence: 99%